EFFECT OF ICT DEPLOYMENT ON THE OPERATIONAL PERFORMANCE OF KENYA REVENUE AUTHORITY - Kairu, Martin M.; Rugami, Mr. Maina (Journal of Strategic Management, 2017)
Purpose: The purpose of the study was to determine the effect of ICT deployment on the operational performance of Kenya Revenue Authority Methodology: The research design used for this study was descriptive survey design. The population of this study was top management, middle management and supervisory employees of Kenya Revenue Authority and who have been with the institution for a minimum period of one year. Data was collected by use questionnaires. The questionnaire consisted of structured closed ended statements. Data was analyzed mainly by use of descriptive and inferential statistics. Descriptive statistics included mode, mean, median, standard deviation. Inferential statistical techniques like correlation coefficients were used to draw a causal relationship between the strategic response and performance. Data was presented by use of graphs, pie charts and tables. Results: Based on the findings, the study concluded that ICT development in KRA management information system is compatible with other systems and flexible enough to support the growth of the firm crucial in assisting employees to enhance their performance. However it is not a significant factor in determining performance of KRA. Adoption of ICT development practices by KRA has increased the access to useful information about best practices of operation. ICT development is important as it enables time saving of operations and increase public access of information. Through ICT KRA has been able to increase their level of transparency. Unique contribution to theory, practice and policy: Based on the findings, the study recommends that KRA and other public institution have to emphasize on the need to develop their technology and customer relationship management. ICT development is of core importance to many organizations in need of growing successfully and improves efficiency in operations and in serving clients.